A mountain of millipedes VIII. The genus Aquattuor Frederiksen, 2013 revisited – a new species from the Udzungwa Mts, Tanzania, another from the Nguru Mts and introduction of the first pair of male legs as a source of taxonomic characters (Diplopoda, Spirostreptida, Odontopygidae) - Enghoff, Henrik (European Journal of Taxonomy, 2020)
A large, newly collected material of the genus Aquattuor from the Udzungwa Mts, Tanzania, has been studied. Two new species are described, viz., A. mollilobus sp. nov. from the Udzungwa Mts and A. nguruensis sp. nov. from the Nguru Mts, Tanzania. Aquattuor claudiahempae Enghoff & Frederiksen, 2015, is recorded as new for the Udzungwa fauna. Characters from the first pair of male legs are illustrated for all Aquattuor species and are shown to be useful for species discrimination. A new gonopodal difference between A. submajor Enghoff, 2015 and A. udzungwensis Enghoff, 2015 is described and illustrated. Intrageneric relationships and distribution patterns are discussed. A distribution map and a key to all Aquattuor species are presented.